Peran Kepemimpinan Kepala Sekolah, Motiva si Guru Dan Dukungan Orang Tua Pada PJJ Masa Pandemi Covid 19 - Sunik Widyaningsih (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
Distance learning is the best step to do so that the learning process can continue during the Covid 19 pandemic. Problems that occur arise student saturation so that many children complain about being lazy and some even don't want to go to school anymore. This study aims to determine leadership role of the principal, teacher motivation and parental support in distance learning at Elementary school 2 Wajak during the Covid 19 pandemic. Distance learning in question is a non-face-to-face learning.This study used a qualitative method with 29 respondents consisting of principals, teachers, guardians and students of Elementary school 2 Wajak. The results of this study indicate the role of the principal in motivating teachers to develop learning methods and models, the limited ability of teachers to develop the distance learning model because it is a new thing. Parents support distance learning activities by providing internet quota for learning. Student assistance during Distance learning is carried out by parents who are not busy at work.School principal must increase they role so they can monitor the implementation of Distance learning, both the methods and models used through the class WA group, while at the same time ensuring that teachers in Distance learning include strengthening character education. It is hoped that if strengthening character education has been instilled, the awareness of students to participate in Distance learning activities will be high, students are increasingly aware that learning is a right, not just an obligation.